The Role of Village-Owned Enterprises in Agriculture Sector in Enhancing Community Welfare in Tampahan District, Toba Regency, North Sumatra - Jef Rudiantho Saragih; Fetty Farida Tamba; Mhd. Asaad (Agro Bali : Agricultural Journal, 2023)
The farming business needs to obtain support to increase the income and welfare of farmers. This study aims to analyze the role of village-owned enterprises (BUM Desa) in agriculture sector in enhancing community’s welfare. The research was conducted in Gurgur Aekraja Village, Tampahan District, Toba Regency, from January to March 2021. 66 farmers were determined as respondents using a simple random sampling. Respondents' perceptions of variable indicators were measured using a Likert scale. The role of BUM Desa is measured based on the influence of the independent variables on the dependent variable with multiple linear regressions. Farmers' perceptions of variable indicators are in the very good category, namely 4.34 for the establishment of BUM Desa, 4.43 for BUM Desa activities, and 4.42 for community welfare. Based on multiple regression analysis, it was concluded that the establishment of BUM Desa and BUM Desa activities plays a very significant role in improving community welfare.